(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Caesarian section is one of the most common operations Now a days for delivery of baby sub-arachnoid block is the better choice. World wide Commonly used bupivacaine with fentanile. Objective The present study was designed to observe the effects of intrathecal ketamine hydrochloride with bupivacaine+complne bupivacaine with fentanyl to observe quality of block eioth duration block during caesarian section. Methods Ninety ASA 1 parturients scheduled for elective caesarian section were randomly selected. There are thirty patients in each group. The base line haemodynamic parameters, heart rate, blood pressure respiratory rate SpO2 and indication of operation were recorded The control group BN (n = 30) received 1.75 ml of 0.5% hyperbaric bupivacaine plus 0.5 ml normal saline intrathecally. While the study group, fentanyl group BF (n = 30) received 1.75 ml of 0.5% hyperbaric bupivacaine plus 0.5 ml (25 mg) injection fentanyl, BK received 1.75 ml of 0.75% hyperbaric bupivacaine plus 0.5 ml (25 mg) of ketamine hydrochloride. Results Duration and quality of sensory and motor block, post-operative analgesia, haemodynamic changes and sedation levels were assessed. There was no significant difference in duration of motor blockade in three groups. Quality of analgesia, sensory block was significant (P<0.05) in BK and BF group than BN group. The quality of block was excellent throughout the surgical procedure in 80% BK group 60% in BF group and 53.3% in control (BN) group. Incidence of hypotension was less in group BF (26.6%) and BK (20%) than group BN (40%). Ketamine had an upper level of sensory block than fentanyl. Conclusion Injection ketamine 25 mg can be used as an adjunct to low dose spinal bupivacaine during caesarian. DOI: http://dx.doi.org/10.3329/jbsa.v24i2.19802 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(2): 53-59